Effect of Low Doses of Guaiacol and Ethanol on Enzymatic Activity of Fungal Cultures - Elżbieta Malarczyk; Anna Jarosz-Wilkołazka; Janina Kochmanska-Rdest (SAGE Publishing, 2003)
The influence of low doses of guaiacol and ethanol, the natural effectors of lignin and phenolics transformations, on laccase and peroxidase activities produced by two strains of Basidiomycetes, Pleurotus sajor-caju and Trametes versicolor , was evaluated. Fungal mycelia were grown for 2 weeks on liquid media containing serial dilutions of guaiacol or ethanol ranging from 100 −1 to 100 −20 mol/L. Laccase and peroxidase activities in the medium were measured at the end of 2 weeks. The effect of low doses of guaiacol and ethanol on enzyme activities was manifested in an oscillating manner. Similar response patterns were observed when pure enzymes were exposed to the same serial dilutions of guaiacol and ethanol. T. versicolor cultures enriched with 40 mmol guaiacol (simulating natural environmental conditions) also displayed oscillating enzyme activity patterns in response to serial dilutions of guaiacol, but the maximum enzyme activity values were increased compared to those observed in cultures not receiving 40 mmol guaiacol. The differences between maxima and minima varied among the experimental groups and depended on the species of fungus, type of effector, and kind of enzyme. The results suggest the possibility of subtle regulation of enzymatic activity on the molecular level.